Family Midwife Care Planning In Ny. T Age 25 Years Old Pi A0 Iud Contraceptor Acceptance With Physiological Leucorea At Siti Kholijah Marelan Clinic - Arnof Yerni; Hilda Yati; Juli Antika; Erika Virgiasari (Institute of Computer Science (IOCS), 2021)
The IUD is a device that is installed in the uterus. The function of this equipment is to change the atmosphere of the endometrial fluid so that there is an increase in macrophages, changes in endometrial fluid are not suitable for spermatozoa to pass through so that many die, many macrophages may kill spermatozoa. Leukorrhea is a fluid that is released from the genitals that is not blood, the fluid contains a lot of leukocytes and the color is slightly yellowish, often thicker and smells good. Able to carry out family planning midwifery care for IUD contraceptive acceptors with leukorrhea using the Varney midwifery management approach. This case study uses a descriptive method, the location is at Siti Kholijah Clinic, Medan Marelan, the subject of the case study is Mrs. T 20 years old P1 A0, this case study was conducted from 20 March – 28 April 2021, Data collection techniques using primary data include physical examination (inspection, palpation, percussion, auscultation), interviews, observations and secondary data including documentation and literature studies. After 6 weeks of care, the results showed that the vaginal discharge experienced by the mother had healed, and there were no potential diagnoses such as vaginal infections, vulvitis, vaginitis and vulvo vaginitis due to proper handling, the mother was willing to keep her genital area clean, the mother said she was happy because she could have intercourse having sexual intercourse with her husband, the mother is willing to re-check in 3 months, namely August 1 2015, the mother is still using the IUD contraception.